Analisis Tingkat Kesukaran Soal Pada Mata Kuliah Akhlak di STAI Assunnah: Penelitian - Febby Adinda; Suchi Nurul Khofifah; Nur Haflisma Lubis; Nurmawati (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The evaluation of learning outcomes plays an important role in determining the success of the educational process, particularly in shaping students’ character and moral values in the Akhlak course. One aspect that needs to be analyzed in evaluation is the level of item difficulty as an indicator of the quality of assessment instruments. This study aims to analyze the level of item difficulty in the Akhlak course at Assunnah Islamic College (Sekolah Tinggi Agama Islam/STAI Assunnah) to determine the extent to which the test items are aligned with students’ abilities and the principles of validity in educational evaluation. The results of the study show that out of 40 test items analyzed, 15 items (37.5%) were classified as easy, 18 items (45%) as moderate, and 7 items (17.5%) as difficult. This distribution indicates that most of the items are at a moderate level of difficulty; however, there are still proportions of items that are too easy and too difficult. Such conditions can affect the validity of test results because not all items are able to optimally discriminate students’ abilities. These findings emphasize the importance of conducting regular item analysis so that evaluation instruments in the Akhlak course become more proportional and are able to measure learning outcomes comprehensively. The results of this study are expected to help lecturers improve the quality of questions by improving indicators, grids, and difficulty calibration.